Graphic warnings and text warning labels on cigarette packages in Riyadh Kingdom of Saudi Arabia: Awareness and perceptions - Jradi, Hoda (Ann Thorac Med, 2018)
BACKGROUND: Graphic warning labels have been shown to be effective in smoking initiation and cessation and were implemented in Saudi Arabia in 2012. To date, no study has assessed the effectiveness of these labels and the Saudi population's perceptions on the effectiveness of cigarette health warning labels. METHODS: We used a cross-sectional qualitative study comprising of nine focus groups among 3 different community group members including health-care workers, adult women and adult men. We conducted in-depth interviews among community leaders. Both focus groups and interviews assessed awareness levels and elicited perceptions about health warning labels on cigarette boxes currently used in the Kingdom of Saudi Arabia. RESULTS: While most participants in the study were aware and supported the use of graphic warning labels on cigarette packages, the awareness of the specific details on the labels was low. Participants perceived the effectiveness of current labels somewhat vague in smoking cessation and advocated for stronger and more aggressive graphics. Community leaders, however, preferred text-only labels and did not support aggressive labels which were deemed culturally and religiously inappropriate. CONCLUSIONS: The study suggests that while graphic warning labels are perceived as necessary on cigarette packages the currently used messages are not clear and therefore do not serve their intended purposes. Measures should be undertaken to ensure that pictorial cigarette labels used in Saudi Arabia are culturally and ethnically appropriate and are rotated on a regular basis to ensure salience among smokers and nonsmokers alike.